Etnobotani Tumbuhan Obat di Desa Mnelalete Kecamatan Amanuban Barat Kabupaten Timor Tengah Selatan (TTS) - Arini Rahma Dhani; M. Ulil Hac D (KOLONI, 2026)
This study aimed to identify the types of medicinal plants, processing methods, and community knowledge regarding the utilization of medicinal plants in Mnelalete Village, South Central Timor Regency. This research used a descriptive method with a qualitative approach and was conducted in March 2025. Data were collected through interviews, observations, and documentation using a purposive sampling technique involving 10 respondents consisting of community leaders, traditional healers/massage therapists, and community members who had knowledge about medicinal plants. The results showed that there were 25 species of medicinal plants belonging to 18 families utilized by the community to treat various diseases, such as wounds, malaria, stomach disorders, tumors, high fever, ringworm, coughs, diarrhea, and other illnesses. The plant parts most commonly used were leaves, fruits, rhizomes, stems, and sap. The methods of processing medicinal plants included boiling, pounding, grating, chewing, burning, and consuming them directly. Community knowledge regarding medicinal plants was inherited from their ancestors and has been maintained until today. The use of medicinal plants is preferred because they are easy to obtain, relatively inexpensive, and considered to have fewer side effects compared to modern medicine. This study is expected to serve as a source of information for the community and educational institutions regarding the importance of preserving and utilizing traditional medicinal plants.